Answer: The answer has one solution:
_______________________________
→ x = 1 ; y = -4 ; or, write as: [1, -4].
_______________________________
Explanation:
_______________________________
Given:
y = - 1x – 3
y = -7x + 3 ;
_______________________________
-1x – 3 = -7x + 3 ; Solve for "x" ;
Add: " +1x" ; and add " +3 " ; to Each Side of the equation:
Subtract " 1x " ; and Subtract " 1 " ; from Each Side of the equation:
-1x + 1x – 3 + 3 = -7x + 1x + 3 + 3 ;
to get:
0 = -6x + 6
↔ -6x + 6 = 0 ;
Now, subtract " 6 " from Each Side of the equation:
-6x + 6 – 6 = 0 – 6 ;
to get:
-6x = -6 ;
Now, divide Each Side of the equation by " -6 ";
to isolate "x" on one side of the equation;
& to solve for "x" ;
-6x /-6 = -6/-6 ;
to get:
x = 1 .
_______________________________
Now, let us solve for "y" ;
We are given:
y = -x – 3 ;
Substitute our solved value for "x" ; which is: " 1 " ; for " x " ; into this given equation; to obtain the value for " y " :
y = -x – 3 ;
= -1 – 3
y = - 4 .
_______________________________
Let us check our answers by plugging the values for "x" and "y" ;
" 1 " ; and " -4 "; respectively); into the second given equation; to see if these values for " x " and " y" ; hold true:
Given: y = - 7x + 3 ;
→ -4 =? -7(1) + 3 ?? ;
→ -4 =? -7 + 3 ?? ;
→ - 4 =? -4 ?? ;
→ Yes!
_______________________________
The answer has one solution:
→ x = 1 ; y = - 4 ; or, write as: [1, -4 ].
_______________________________
Hope this is helpful! Best wishes!
_______________________________